Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.060
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception of Bajo Tribe Women on High-Risk Pregnancy

Abstract: Every day more than 830 mothers die from diseases related to pregnancy and childbirth, 99% of maternal mortality rate (MMR) occurs in developing countries and in poor communities. Risk factors for 75% of maternal deaths are caused by severe postpartum bleeding, postpartum infections, high blood pressure during pregnancy (eclampsia), prolonged / obstructed labor which caused by narrow pelvic, or the baby breech location. Maternal mortality rate in Indonesia is 305 which is the highest in ASEAN countries (SUPAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Another study stated that women in rural area tend to choose traditional birth attendants to facilitating their delivery at home because they has more experience is assisting childbirth and more patient in caring for women in labor. Traditional birth attendants will wait for women from the initiation phase of the delivery process until will not set a price in providing their services, which is different from health workerd which already set a price for every services (18).…”
Section: Ethical Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study stated that women in rural area tend to choose traditional birth attendants to facilitating their delivery at home because they has more experience is assisting childbirth and more patient in caring for women in labor. Traditional birth attendants will wait for women from the initiation phase of the delivery process until will not set a price in providing their services, which is different from health workerd which already set a price for every services (18).…”
Section: Ethical Statementmentioning
confidence: 99%
“…The higher level of the family's economy, the easier access to health services will be. Families with low income are unable to provide funds for antenatal care until delivery (18).…”
Section: Ethical Statementmentioning
confidence: 99%
“…F. A. Gobel et al (2020) reported that for the Bajo people, the education that should not be lost is the value that is taught from generation to generation, and this should not be lost from the lives of their children and grandchildren. At the same time, formal education is not seen as necessary, so finishing elementary school (SD) is enough.…”
Section: Figure 1 An Overview Of the Bajo Village Areamentioning
confidence: 99%
“…Namun dalam pelaksanaannya, diperlukan kematangan emosi dan kedewasaan sehingga kelangsungan pernikahannya dapat terjaga dengan baik (2) Pola perilaku budaya yang diturunkan dari generasi ke generasi memberikan kerangka kerja konseptual untuk memahami esensi dari semua perilaku manusia, dukun atau Sandro masih dipercaya oleh masyarakat dapat menyelesaikan segala permasalahan yang dihadapi. (3) Penyebab pernikahan usia dini antara lain pemaksaan dari pihak orang tua, pergaulan bebas, rasa keingintahuan tentang dunia seks, faktor lingkungan, rendahnya pendidikan, faktor ekonomi. Ditinjau dari masalah sosial ekonomi adalah pernikahan usia dini biasanya tidak diikuti dengan kesiapan keadaan ekonomi.…”
Section: Pendahuluanunclassified